Integrative and complementary practices in the care of health workers: a scoping review (Research, Society and Development, 2023)
Stress is considered a global epidemic that affects more than 90% of the population, with harmful health consequences. Health workers account for most of these cases, which was evident during the Covid-19 pandemic. In this context, investment in actions to promote workers' health, such as Integrative and Complementary Practices in Health (PICS), become powerful tools for care and improvement of quality of life. Objective: To map in the global literature the use of PICS for the care of health workers. Methods: Scope review was performed with a search in the information sources of scientific literature, in the period from October to November 2021. The process of selecting the studies was done by two reviewers, independently. Data was collected by one reviewer and checked by another. Results: Of 32 studies included, half are systematic reviews. Most studies were conducted in hospital and outpatient settings, with mainly nursing participants, and the mindfulness practice presented more robust evidence. Conclusions: Findings show that PICS are powerful tools for health workers care. However, to be effective they need to be compatible with work schedules.